Inequalities, exclusion and COVID-19 in Sub-Saharan Africa - Raymond Boadi Frempong; Jacob Novignon; David Stadelmann (Center for Research in Economics, Management and the Arts (CREMA), 2021)
Since the outbreak of the COVID-19 crisis, there is an increased interest to understand how social inequalities, discrimination, and inclusion are related to the pandemic. Sub-Saharan Africa has been comparatively resilient regarding the number of cases and fatalities per capita. At the same time, the region has high rates of multiple inequalities. Socioeconomic inequalities could adversely affect the fight against COVID-19 by influencing people's access to healthcare and eroding confidence and trust in public health institutions. This work investigates the effects of education, gender, income, and political inequalities on COVID-19 in Sub-Saharan Africa. The study also explores a country case study from Ghana to complement the systematic regional analysis. We find that pre-existing income inequality, along with some other dimensions of inequality, may have contributed to higher infection and mortality rates of COVID-19. We recommend that in the shortterm governments should consider outcomes of inequality in their fight against COVID-19. In the medium and long-term, and for the effectiveness of measures to fight future outbreaks, governments should strive to reduce various forms of inequalities.
Keywords: 330; COVID-19; Inequality; Sub-Saharan Africa